Sustainability Leadership: The Role of Strategic Management in Achieving Sustainable Competitive Advantage - Adya Hermawati; Rizki Dwi Ariyanto; Tri Wartono; Kanisius Bruno Siki (PT. Anagata Sembagi Education, 2025)
This study investigates the role of sustainability leadership in shaping strategic management practices and their combined impact on achieving sustainable competitive advantage. Using a quantitative design with data from 230 managers and sustainability practitioners in Indonesia, the research employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationships among Sustainability Leadership (SL), Strategic Management (SM), and Sustainable Competitive Advantage (SCA). The findings reveal that SL has a significant positive effect on SM (β = 0.768, p < 0.001), and SM has a strong effect on SCA (β = 0.542, p < 0.001), confirming SM’s mediating role in the SL–SCA relationship. These results underscore that sustainability-oriented leadership enhances organizational innovation, stakeholder engagement, and adaptability through structured strategic mechanisms. The study contributes theoretically by integrating the Resource-Based View (RBV) and Natural Resource-Based View (NRBV) frameworks, demonstrating that leadership and strategy function as dynamic capabilities that reconfigure internal competencies for superior sustainable performance. Practically, the results suggest that organizations embedding ethical, visionary, and transformational leadership into strategic processes are more capable of achieving long-term competitiveness in the era of the green economy and digital transformation.